Somatostatin-positive GABA Interneuron Deficits in Depression: Cortical Microcircuit and Therapeutic Perspectives - Fee, Corey (Biol Psychiatry, 2017)
The functional integration of external and internal signals forms the basis of information processing and is essential for higher cognitive functions. This occurs in finely-tuned cortical microcircuits whose functions are balanced at the cellular level by excitatory glutamatergic pyramidal neurons and inhibitory γ-aminobutyric acid (GABA) interneurons. The balance of excitation and inhibition, from cellular processes to neural network activity, is characteristically disrupted in multiple neuropsychiatric disorders, including major depressive disorder (MDD), bipolar disorder (BPD), anxiety disorders, and schizophrenia (SCZ). Specifically, nearly three decades of research demonstrate a role for reduced inhibitory GABA level and function across disorders. In MDD, recent evidence from human postmortem and animal studies suggests a selective vulnerability of GABAergic interneurons that co-express the neuropeptide somatostatin (“SST cells/interneurons”). Advances in cell type-specific molecular genetics have now helped to elucidate several important roles for SST interneurons in cortical processing (regulation of pyramidal cell excitatory input) and behavioral control (mood and cognition). Here, we review evidence for altered inhibitory function arising from GABAergic deficits across disorders, and specifically in MDD. We then focus on properties of the cortical microcircuit, wherein SST-positive GABA interneuron deficits may disrupt functioning in several ways. Finally, we discuss the putative origins of SST cell deficits, as informed by recent research, and implications for therapeutic approaches. We conclude that deficits in SST interneurons represent a contributing cellular pathology, and therefore a promising target for normalizing altered inhibitory function in MDD and other disorders with reduced SST cell and GABA functions.